2005
DOI: 10.1088/0031-9155/50/22/003
|View full text |Cite
|
Sign up to set email alerts
|

Fricke gel as a tool for dose distribution verification: optimization and characterization

Abstract: With the introduction of conformal techniques in radiation therapy, gel dosimetry plays an important role as a 3D dose verification system. There are two main types of gels in use for dosimetry: Fricke gels and polymer gels. The advantages of polymer gels are improved dose response and stability with no diffusion problems. However, the more complicated fabrication procedure and the greater cost compared to Fricke gels makes polymer gels less attractive in routine clinical use. Dose resolution has recently been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Fricke gels are an interesting alternative for 3D dosimetry of MRgRT systems as these dosimeters could be read out by the MRI system during or immediately after irradiation without moving the dosimeter from the treatment device to an auxiliary imaging system [21]. Compared to optical CT read-out, the Fricke dosimeter thus eliminates positioning errors associated with pre-and post-scanning, and the known limitations of diffusion-induced dose smearing for these dosimeters [22] may be of less importance for the described workflow.…”
Section: Discussionmentioning
confidence: 99%
“…Fricke gels are an interesting alternative for 3D dosimetry of MRgRT systems as these dosimeters could be read out by the MRI system during or immediately after irradiation without moving the dosimeter from the treatment device to an auxiliary imaging system [21]. Compared to optical CT read-out, the Fricke dosimeter thus eliminates positioning errors associated with pre-and post-scanning, and the known limitations of diffusion-induced dose smearing for these dosimeters [22] may be of less importance for the described workflow.…”
Section: Discussionmentioning
confidence: 99%
“…A number of research groups has reported good results comparing planned and measured dose distributions in 3D. 29,105,137 While being able to directly…”
Section: Dose Verification In Radiotherapymentioning
confidence: 99%
“…Fricke and polymer gel dosimetry has emerged as a suitable tool to measure three-dimensional dose distribution for complex delivery verification and quality assurance of modern radiotherapy techniques such as IMRT. [ 1 2 ] For external-beam radiotherapy international protocol recommend calibration be carried out in terms of absorbed dose to water. [ 3 ] Therefore, it is preferable to use a gel dosimeter with the composition to be very close to that of water.…”
Section: Introductionmentioning
confidence: 99%